Educational needs of primary school children about accident prevention - Ziani, F (Iran University of Medical Sciences, 1995)
Accidents are one of the mortality reasons and most important agents of disability in primary school children. In this research, educational needs of 10-12 years old children who studied in fourth and fifth class in governmental primary schools of Tehran city about accident prevention are assessed by questionnaire. Results showed that majority of children had correct performance and had low educational needs about accident prevention related to passing across the street, automobile riding, bicycle riding, using of igniting instruments, playing with perilous toys, playing in unsafe places and swimming. Also, statistical tests showed that boys in comparison with girls had more educational need. When age and educational level of mothers are increased, educational needs of them are reduced. Also, when number of children and birth rank of child are increased, educational needs of them are increased